Assessing the impact of YouMatter Protocol for Physical and Mental Well-Being (YMPPMW) on Mental Health - Tambe, Abhishek; Mohammad, Shamim; Saloni, Saloni; Bhansali, Heenakshi (Journal of Neonatal Surgery, 2025)
Despite great progress and active work in the field today, mental health disorders continue to be a global health issue. On two sides of the equation, however, we’ve made a lot of progress towards meeting physical and psychological care, which leaves us still deficient in the middle, and patients still trying to glue together their own total wellbeing from scraps. YMPPMW is an integrated solution in the form of physical therapy and evidence based psychological interventions to individuals serving the entire landscape of needs. Mental health aspect of YMPPMW was explored with a focus on the fact YMPPMW uses a unique dual approach to interventions, i.e. physical therapy interventions such as stretching, strengthening and range of motion (ROM) exercises as well as psychotherapy interventions such as cognitive behavioural therapy, vagus nerve stimulation and mindfulness practices. This research was based on the use of the mixed method design to evaluate the impact of YMPPWM in the mental health outcomes. To assess the parameters of anxiety, depression, and perceived stress, quantitative data collection was carried out using validated psychological scales pre and post intervention period. In addition, qualitative methods permitted for story conveying through the participants, emotional regulation, resilience, as well as general wellness of a participant. The structured intervention was a four week intervention which had thrown progress to the participants parameter and keep monitoring and also provided feedback on the same. Preliminary results show that people are getting big benefits to their mental health, reporting less symptomatology for anxiety and depression, better emotional regulation, among other things, improved stress management. Participants got more aware of themselves, and they managed to achieve control over their mental health, and even experienced a physical effect, i.e. structure flexibility and muscles discharge. As such, the importance of YMPPMW as a gap bridge of mind and body was signalled as integration of mind and body health as embodied in it. This study shows that YMPPMW is an all in one mental health care therapy. It is important for this to be extended to examine the extent in which this work is effective over the long term, what support may be needed to sustain this work over time, how scalable and applicable across the diverse population, and to explore additional clinical and non clinical applications that might be identified as it relates to potential utility in advancing mental health or wellness overall.